Apuntes sobre la alteridad constituyente en los Andes. Ambivalencias rituales y lingüísticas sobre un espacio imaginario - Rivera Andía, Juan Javier (Revista Española de Antropología Americana, 2008)
In this article I will show the perception that the inhabitants of the Lima Highlands have, as participants of a ritual, have about a particular space: the mountains that surround the peasant villages. This approach will be done first through the spatial division implicit in a very widespread ceremony of the Andes: the cattle branding ritual. What is this celebration telling us about the mountains where the cattle stay during the biggest part of the year? In second place, I will explore the connotations of a word that designates the human inhabitant of this space: the llakwash.